Combating childhood obesity: lessons learned from a student extension project - Firpe, Esther Emanuele; Bretas de Matos, Laura Clara; Shamash Amorim, Davi; Soares Corrêa , Ellen; Quintanilha Scofield da Silva, Gabriela; Dias Silva, Jessica Ariane; Araújo de Faria, Júlia Gabriela; Teixeira Carvalho Mota, Júlia; Girardelli Caires Vidal , Lara; Soares Corrêa , Livia; Reis Aroeira, Luiza; Pereira Lima, Maria Cecília; et al. (Guará Journal, 2025)
Obesity is a multifactorial disease characterized by the excessive accumulation of adipose tissue throughout the body. In the Brazilian pediatric population, one in every three patients aged between 5 and 10 years is above the ideal weight threshold. Therefore, the extension project "Childhood Obesity: Intervention and Care for the Child's Future" was developed to provide guidance on appropriate nutritional strategies tailored to the age group of children/adolescents and emphasize the importance of physical activity combined with dietary habit modifications to yield optimal outcomes. This is an experience report based on the perceptions of medical and nursing students engaged in extension activities at the pediatric outpatient clinic. Throughout the project, a total of 165 children were engaged by 13 extension students. The students addressed various topics, such as weight loss strategies among pediatric patients and their families, including the significance of physical activity and the implementation of the Traffic Light Diet as a means to enhance dietary quality. Socioeconomic challenges, such as insufficient financial resources, were identified by the students, constituting a barrier to the performance of healthier habits.
Keywords: Pediatric Obesity; Primary Prevention; Feeding Behavior